Cost of ending hunger: Consequences of complacency, and financial needs for SDG2 achievement - Joachim von Braun; Bezawit Beyene Chichaibelu; David Laborde Debucquet; Máximo Torero (University of Bonn, Center for Development Research (ZEF), 2024)
The number of hungry and malnourished people in the world remains unacceptably high. Achieving Sustainable Development Goal 2 (SDG2: Zero Hunger) by 2030 is moving increasingly out of reach, despite ongoing and widely publicized national, regional and global policy efforts to make progress (e.g. G7, G20 and the UN Food Systems Summit and its follow-up processes). In 2022, 9 percent of the global population (735 million people) were undernourished and 30 percent (2.4 billion people) faced moderate or severe food insecurity. Africa, in particular, stands out with persistently higher levels of food insecurity compared to the global average. This is especially the case for rural populations and women. The world is also not on track to achieve the 2030 targets for child stunting, child overweight, child wasting and low birthweight, important indicators of severe malnutrition. [...]
Keywords: 330